Effect of L. reuteri on bowel movements in children aged 6 months to 4 years: A double-blind randomized controlled trial - Jung, Camille; Kalach, Nicolas; Degas, Vanessa; Jeridi, Yasmine; Bertrand, Valérie; Bellaiche, Marc (Frontiers in Pediatrics, 2022)
Background: Chronic constipation is common in children and often requires prolonged laxative treatment. Preliminary studies suggest that the probiotic Limosilactobacillus reuteri (L. reuteri) may be useful in treating constipation in children, but these preliminary results need to be replicated. The objective of this study was to assess the efficacy of L. reuteri in infants and young children with chronic functional constipation. Methods: A prospective double-blind randomized placebo-controlled trial was conducted in 5 pediatric departments in France between June 2017 and June 2021. In all, 49 patients—ages 6 months to 4 years, and suffering from chronic constipation per Rome IV criteria—were randomly allocated to the test and control groups. For 4 weeks, all were orally administered 5 daily drops of the test (L. reuteri DSM 17938 at 108 colony-forming units per day) or control (placebo) treatment, respectively. Participants were clinically assessed at 4 and 8 weeks. Parents were asked to daily record the number of spontaneous bowel movements (SBMs), stool consistency, and the use of any additional laxatives. Informed consent was obtained from parents of all recruited patients, and the study was approved by both an ethics committee and the French National Agency for Medicines and Health Products Safety (ANSM). The study is registered on ClinicalTrials.gov (NCT03030664). Results: The change in SBMs relative to baseline was greater in the control group at week 4 (control: 0.27 ± 0.5; test: 0.23 ± 0.5; P = 0.01) and in the test group at week 8 (control: 0.26 ± 0.4; test: 0.22 ± 0.5; P = 0.03). At week 4, the groups did not differ in number of responders (≥3 stools per week, with no non-retentive fecal incontinence), use of rescue medication, scoring of pain during defecation (Faces Pain Scale–Revised), or stool consistency (Bristol Stool Form Scale). Conclusion: This double-blind randomized controlled trial did not confirm the efficacy of L. reuteri for treatment of chronic functional constipation in young children.